Arab Prisoners In Medieval Byzantium And Their Efforts In Historical Documentation (Journal of the College of Basic Education, 2026)
The research sheds light on an image of Arab-Islamic creativity in historical documentation through the efforts of Arab Muslim prisoners in documenting the history of the Byzantine Empire in the third century AH/ninth century AD, as they were prisoners of war in the prisons of this empire, by drawing the image of the prisoner, writer, historian in documenting the history of neighboring peoples with complete freedom and honesty, The research focused on the efforts of two Muslim prisoners, Muslim al-Jarmi and Harun ibn Yahya. Their writings revealed the different ways and perspectives of Byzantine civilization, which were diverse and comprehensive, and benefited historical research in documenting that era.